Observability of Nonlinear Fractional Dynamical Systems. (24th June 2013) - Balachandran, K.; Govindaraj, V.; Rivero, M.; Tenreiro Machado, J. A.; Trujillo, J. J.
Abstract : We study the observability of linear and nonlinear fractional differential systems of order 0 < α < 1 by using the Mittag-Leffler matrix function and the application of Banach's contraction mapping theorem. Several examples illustrate the concepts.